Differential effects of sevoflurane and propofol on swine cardiac conduction system. (May 2019) - Zaballos, Matilde; Del Blanco, Brezo; Sevilla, Raul; De Diego, Carlos; Anadon, M José; Jimeno, Concepción; Almendral, Jesús
Abstract: Objective: To compare the effects of sevoflurane and propofol on the porcine cardiac conduction system. Study design: A prospective, comparative study of electrophysiological properties of anaesthetics agents in an experimental porcine model. Animals: A total of 36 hybrid Landrace-Large White pigs. Methods: After premedication with 20 mg kg −1 of intramuscular ketamine, anaesthesia was induced with 4.5 mg kg −1 propofol intravenously. In 18 consecutive animals, anaesthesia was maintained with propofol (13 mg kg −1 hour −1 ) and in the remaining 18 animals with 2.66% sevoflurane. The femoral artery and vein were canalized for invasive monitoring, analytical blood gas sampling and intracardiac catheter insertion. Following instrumentation and after a period of stabilization, a customary electrophysiological evaluation was performed. We compared the electrophysiology of the sinus and atrioventricular node (AV) node under sevoflurane or propofol anaesthesia, and the effects of both anaesthetics on atrial and ventricular refractoriness. Results: There was a significant difference in sinus node recovery time between sevoflurane and propofol (907 ± 231 versus 753 ± 146 ms, p  = 0.02). Sevoflurane in comparison with propofol significantly prolonged specialized AV conduction times, represented by an increased Wenckebach cycle length (272 ± 54 versus 235 ± 40 ms, p  = 0.03) and AV nodal refractoriness (327 ± 34 versus 287 ± 30 ms, p  = 0.002). In addition, sevoflurane prolonged ventricular refractoriness (298 ± 27 versus 255 ± 38 ms, p  = 0.007) and the QT corrected interval (0.50 ± 0.05 versus 0.46 ± 0.09 ms, p  = 0.005). Conclusions and clinical relevance: Sevoflurane in comparison with propofol, depresses several parameters of sinus and AV nodal function and prolongs the ventricular refractoriness of the porcine cardiac conduction system. These findings should be taken into consideration for the choice of anaesthetic agents in clinical and experimental settings.